Transformations of cultural style in Kurdish poetry; Latif Halmat poet was a model - األستاذ الدکتور كاظم فاخر حاجم الخفاجي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research deals with the transformations of the cultural style in the poems of the Kurdish poet Latif Helmet, the that reflect the artist's struggle with his culture, and reveals the Jihad of the pioneering spirit on the two levels: the apparent and the inculcated, and the research as it adopts procedural cultural criticism does not fall captive to his speeches, The basis on which it was based, based on the examination of the living matter that was treated here, is a difficult test for the theory of this new critical approach, as if some cultural criticisms are being presented as a cultural pattern that may not be, and may be a general human being. The research also dealt with the stage of modern poetry second, which was represented by one of the Kurdish poets who were preoccupied with the modernity of the poetic text, what he called "Edward Said" (secularism of the text), and perhaps because of this worldliness and attention to it, Hamlet raised the poetic text that he writes to the rank that makes it Among the best produced by modern Kurdish poets, and that is why we chose it, to be the example through which we discuss the changes of cultural style in these poems. The research included the following points: